A direct one-step synthesis of ultrathin g-C3N4 nanosheets from thiourea for boosting solar photocatalytic H2 evolution. (15th March 2019) - Hong, Yuanzhi; Liu, Enli; Shi, Junyou; Lin, Xue; Sheng, Lizhi; Zhang, Ming; Wang, Longyan; Chen, Jiahui
Abstract: Two-dimensional (2D) graphitic carbon nitride (g-C3 N4 ) nanosheets, as the promising photocatalyst with fascinating properties, have become a "rising star" in the field of photocatalysis. Although g-C3 N4 nanosheets exfoliated from the bulk g-C3 N4 powders are extensively emerged, developing a simple synthetic approach is still full of challenge. To this end, here we report a direct polymerization strategy to fabricate the ultrathin g-C3 N4 nanosheets, that is only heating treatment of thiourea in air without addition of any template. The photocatalytic activities of as-prepared samples were evaluated by photoreduction of water to hydrogen (H2 ) using triethanolamine as sacrificial agent and Pt as co-catalyst under visible-light irradiation (λ > 420 nm). As a result, our few-layered g-C3 N4 nanosheets with an average thickness of 3.5 nm exhibit a superior visible-light photocatalytic H2 evolution rate (HER) of 1391 μmol g −1 h −1 and a remarkable apparent quantum efficiency of 6.6% at 420 nm. Eventually, the HER of as-fabricated ultrathin g-C3 N4 nanosheets is not only much higher than the dicyandiamide-derived g-C3 N4 or melamine-derived g-C3 N4, but also greater than the thermal-oxidation etched g-C3 N4 nanosheets under the same condition. Graphical abstract: Image 1 Herein, we report a one-step but template-free polymerization strategy to fabricate the ultrathin g-C3 N4 nanosheets for boosting visible-light photocatalytic H2 evolution. Highlights: The ultrathin g-C3 N4 nanosheets are firstly prepared by polymerization of thiourea. The g-C3 N4 nanosheets exhibit a greatly improved performance for H2 evolution. The g-C3 N4 (580)-T shows excellent photoactivity and high photochemical stability. The 2D nanomaterials can use as a promising candidate for solar-to-H2 conversion.